Schistosomiasis control using piplartine against Biomphalaria glabrata at different developmental stages. - Ludmila Nakamura Rapado; Alessandro de Sá Pinheiro; Priscila Orechio de Moraes Victor Lopes; Harold Hilarion Fokoue; Marcus Tullius Scotti; Joaquim Vogt Marques; Fernanda Pires Ohlweiler; Sueli Ivone Borrely; Carlos Alberto de Bragança Pereira; Massuo Jorge Kato; Eliana Nakano; Lydia Fumiko Yamaguchi (Public Library of Science (PLoS), 2013)
BACKGROUND: Schistosomiasis is one of the most significant diseases in tropical countries and affects almost 200 million people worldwide. The application of molluscicides to eliminate the parasite's intermediate host, Biomphalaria glabrata, from infected water supplies is one strategy currently being used to control the disease. Previous studies have shown a potent molluscicidal activity of crude extracts from Piper species, with extracts from Piper tuberculatum being among the most active. METHODS AND FINDINGS: The molluscicidal activity of P. tuberculatum was monitored on methanolic extracts from different organs (roots, leaves, fruit and stems). The compounds responsible for the molluscicidal activity were identified using (1)H NMR and ESIMS data and multivariate analyses, including principal component analysis and partial least squares. These results indicated that the high molluscicidal activity displayed by root extracts (LC50 20.28 µg/ml) was due to the presence of piplartine, a well-known biologically-active amide. Piplartine was isolated from P. tuberculatum root extracts, and the molluscicidal activity of this compound on adults and embryos of B. glabrata was determined. The compound displayed potent activity against all developmental stages of B. glabrata. Next, the environmental toxicity of piplartine was evaluated using the microcrustacean Daphnia similis (LC50 7.32 µg/ml) and the fish Danio rerio (1.69 µg/ml). The toxicity to these organisms was less compared with the toxicity of niclosamide, a commercial molluscicide. CONCLUSIONS: The development of a new, natural molluscicide is highly desirable, particularly because the commercially available molluscicide niclosamide is highly toxic to some organisms in the environment (LC50 0.25 µg/ml to D. similis and 0.12 µg/ml to D. rerio). Thus, piplartine is a potential candidate for a natural molluscicide that has been extracted from a tropical plant species and showed less toxic to environment.